2017
DOI: 10.4172/2254-609x.100077
|View full text |Cite
|
Sign up to set email alerts
|

Mother’s knowledge and Practice about Neonatal Danger Signs and Associated Factors in Wolkite Town, Gurage Zone, SNNPR, Ethiopia, 2017

Abstract: Background: Neonates are more prone to show subtle signs of illness. Most infants are either born at home or are discharged from the health facility early, families should be able to recognize signs of newborn illnesses and bring the newborn infant to the attention of a health worker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 0 publications
12
51
3
Order By: Relevance
“…Comparably, in the overall model of mothers' knowledge neonatal danger sign, mothers who had to give birth four and above had two times more likely knowledgeable about neonatal danger sign than mothers who gave birth two up to four times. This finding was supported by studies in Egypt showed, mothers being primi Para are more likely to have poor knowledge about newborn care than multi parity [18]. This study has shown the age of the newborn was found to be a determinant to affect knowledge of neonatal danger sign at home delivered mothers'.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Comparably, in the overall model of mothers' knowledge neonatal danger sign, mothers who had to give birth four and above had two times more likely knowledgeable about neonatal danger sign than mothers who gave birth two up to four times. This finding was supported by studies in Egypt showed, mothers being primi Para are more likely to have poor knowledge about newborn care than multi parity [18]. This study has shown the age of the newborn was found to be a determinant to affect knowledge of neonatal danger sign at home delivered mothers'.…”
Section: Discussionsupporting
confidence: 59%
“…The total sample of the study was determined by using a double population proportion formula. Mother's knowledge of neonatal dangers sign was determined by calculating for factors with Epi-info version 7.0 by taking factors from previous findings in Welkite town 41% [18], 95% confidence level (1.96), Power 80%. The sample size without design effect and non-response rate was calculated as -206 +206 = 412.By considering the 1.5 design effect it was calculated as -412X 1.5 =.Then considering 5% non-response rate:-618+32 = 650.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…1). The town has an elevation between 1910 and 1935 meters above sea level [12,13]. Based on the 2007 Census conducted by the Central Statistical Agency of Ethiopia, Wolkite town has a total population of 28,856 of whom 15,068 were males and 13,788 females [14].…”
Section: Study Area and Study Populationmentioning
confidence: 99%
“…8 Some other studies reported that diarrhea and pus drainage from the eye are considered as neonatal danger signs. [9][10][11][12] Mother's knowledge of neonatal danger signs and healthseeking practices is low in resource-limited countries. 13 Lack of formal links between the local community and health facilities contributes to the inadequate level of mother's knowledge of neonatal danger signs and health-seeking practices.…”
Section: Introductionmentioning
confidence: 99%